Building Games with Ethereum Smart Contracts Intermediate Projects for Solidity Developers - Iyer, Kedar (Apress, 2018)
Learn how to take your existing knowledge of Ethereum and Solidity to the next level. Hone your development skills and become more familiar with the syntax of the Solidity language by working through well-tested, well-documented intermediate-level sample projects. You will begin by covering the basics of Ethereum, Solidity and gaming theory. From there you will move onto sample projects that use smart contract engineering to create fun casino-style games that you can deploy and test on your friends and colleagues with real ether. All games are provably fair and auditable, so that players know the house won't always win! Ideal for any reader with exposure to Ethereum, the techniques this book teaches are applicable to game developers, software engineers, web developers, and cryptocurrency enthusiasts.